Pengembangan Bahan Ajar Elektronik Berbasis Flip Pdf Proffesional Materi Peralatan Penyajian Makanan dan Minuman pada Siswa SMK - Fikri, Muhammad Dhiyaul; Handajani, Sri; Pangesthi, Lucia Tri; Purwidiani, Niken (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to find out: 1) The results of the development of electronic teaching Materials in Food and Beverage Serving Materials; 2) Knowing the eligibility results; 3) Knowing the student's response. ADDIE (Analysis, Design, Development, Implementation or Delivery and Evaluations) development research model. However, the researcher only carried out up to the 3rd stage, namely Development. The data collection technique was questionnaire and involved 2 material validators, 2 media valdators, and also phase F students of SMK Negeri 3 Kediri. The results of the study showed: 1) the results of the e-Module of food and beverage serving equipment material in the form of links; 2) feasibility results with an average score of 95% (very good) from material experts and 97% (very good) from media experts; and 3) student responses with an average score of 86% (very good). This proves that the e-Module of the research results can be used in learning.